Qhapaq Ñan Inkastraßen im Wandel der Zeit - Pointecker, Marco (LIT Verlag GmbH & Co. KG, 2015)
Qhapaq Ñan, refers to a network of roads built during the time of the great inca empire. Almost 55,000 kilometers long this net of roads extended across the entire geographical area of the Inca. The Thesis, that guides this study, is that selected parts of the Qhapaq Ñan could be used for touristic use, presuming this tourism follows sustainable criteria. Not mass tourism but rather innovative programs with a concept that focuses on the balance between "use and protection" of these sensitive areas, will be essential., operated by the local communities could be the right way.